Learning outcomes of basic volleyball techniques through traditional and regional sports - Febrianto, David Galih; Wahyudi, Agung (Universitas Jambi, Indonesia, 2025)
This research aimed to determine the factors and results of the influence of using traditional game methods on the learning outcomes of volleyball games. The traditional game method used in this research was a 2 x 2 factorial design. The research population was SMA Negeri 1 Porwodadi class 11, totaling 32 male and female students. The sample was obtained randomly and divided into two experimental groups. This consisted of 32 students. The data were obtained through five kinds of volleyball playing skills tests. This research concluded that (1) modification of learning media has a significant effect when compared to modification of volleyball game rules, (2) between modification of learning media and gender, there is a significant interaction, and (3) for male students, modification of learning media has a more significant effect when compared to traditional game methods in volleyball games, and (4) for students, traditional game methods have a more significant effect when compared to other rule methods in volleyball games.